EFFECTS OF ANTI-OBSESSIONAL TREATMENT ON PITUITARY VOLUMES IN OBSESSIVE-COMPULSIVE DISORDER - Atmaca, Murad; Yildirim, Hanefi; Mermi, Osman; Gurok, M. Gurkan (Medicinska Naklada, 2016)
Background: We aimed to examine the effct of anti-obsessional drugs on pituitary gland volumes in the patients with obsessive-compulsive disorder (OCD). Subjects and methods: A group of patients with OCD and of healthy controls were evaluated by using pituitary gland magnetic resonance imaging (MRI) at baseline and after twelve weeks of treatment with selective serotonin re-uptake inhibitors or clomipramine. Results: Pituitary gland volumes were found to be statistically significantly smaller in the patients with OCD compared to healthy control subjects at the beginning of the study. We found that pituitary volumes significantly increased throughout twelve weeks of treatment. Conclusions: This study provides an evidence of the effect of anti-obsessional treatment on the volumes of pituitary gland in OCD patients.
Keywords: anti-obsessional; OCD; pituitary gland; SSRI